The platelet-to-high-density lipoprotein cholesterol ratio as a potential biomarker linking tobacco exposure to accelerated reproductive aging in women - Jie Liao; De Qiong; Dawa Zhuoma; Weiwei Ning; Da Ga; Silang Quncuo; Jing Jing; Lingxiu Li; Yalan Li; Xin Li; Bin Lv; Hengxi Chen (Medicine, 2026)
Female reproductive aging, commonly reflected by menopausal age and reproductive lifespan, is influenced by environmental exposures and metabolic health, and tobacco exposure has been associated with earlier menopause and shortened reproductive lifespan. Because this association may involve inflammatory activation and lipid-metabolic alterations, the platelet-to-high-density lipoprotein cholesterol ratio (PHR) may provide a useful composite marker for evaluating tobacco-related reproductive aging. We analyzed data from 6048 women in the US National Health and Nutrition Examination Survey (1999–2018). Serum cotinine and PHR were ln-transformed. Weighted multivariable linear regression assessed associations with menopausal age and reproductive lifespan, adjusting for demographic, lifestyle, and clinical covariates. Exploratory statistical mediation analysis was used to examine the extent to which PHR was statistically related to the association between cotinine and reproductive aging. Restricted cubic splines explored dose-response patterns and possible threshold effects. Higher serum cotinine and PHR were independently associated with earlier menopause (β = −0.28 and −1.86) and shorter reproductive lifespan (β = −0.26 and −1.91; all P < .001). A modest statistically mediated proportion attributed to PHR was observed, accounting for 5.69% to 6.08% of the cotinine-related association. Dose-response analyses suggested possible thresholds (ln-cotinine > −3.47; ln-PHR > 5.13), above which adverse associations became more apparent. Associations were stronger among younger, non-Hispanic White, nondiabetic, and non-hypertensive women. Our study suggests that PHR may be a potentially useful biomarker associated with female reproductive aging. Higher serum cotinine and PHR were associated with earlier menopause and shorter reproductive lifespan, and PHR showed a modest, statistically mediated proportion in these associations. The observed thresholds may be useful primarily for hypothesis generation and future validation, but prospective or longitudinal studies are needed to clarify the potential role of PHR in reproductive aging.